Multiwavelength Random Fiber Laser Based On Dual-Bidirectional SOA at Different Comb Filters - Lah A.A.A.; David A.P.; Aliza H.E.M.; Yusoff N.M.; Ambran S.; Sulaiman A.H.; Salleh M.S. (Institute of Electrical and Electronics Engineers Inc., 2024)
We successfully demonstrated and investigated the lasing performance of multiwavelength random fiber laser (MWRFL) using dual bidirectional semiconductor optical amplifiers (SOA) with Mach-Zehnder interferometer (MZI)based on polarization maintaining fiber (PMF) and Sagnac loop mirror (SLM). This work provides a thorough understanding on the MWRFL performance, and it is beneficial in determining the suitable comb filters to be used depending on the applications. The PMF-based MZI generated 50 lasing lines within the 3 dB bandwidth flatness. The lasing peak power is 19.1 dBm with an extinction ratio (ER) of 11.65 dB, and peak power deviations of 0.17 dB. The SLM produced 45 lasing lines within the 3 dB bandwidth flatness. The peak power is -17.6 dBm with an ER of 12.7 dB and peak power deviations of 0.11 dB. Tuning of the polarization controller plate can change the MWRFL performance. The PC plate adjustment in PMF-based MZI can increase the ER up to 61% while in SLM, the ER value is triple. Even though the SLM has a lower number of lasing lines compared to the PMF-based MZI, however, it has a higher ER value and better lasing stability within 120 minutes. 2023 IEEE.